胸腺切除范围对早期胸腺上皮肿瘤预后的影响 (Zhongguo Fei Ai Za Zhi, 2016)
BACKGROUND AND OBJECTIVE: To evaluate the surgical outcomes of tumor resection with or without total thymectomy for thymic epithelial tumors (TETs) using the Chinese Alliance for Research in Thymomas (ChART) retrospective database. METHODS: Patients without preoperative therapy, who underwent surgery for early-stage (Masaoka-Koga stage Ⅰ and Ⅱ) tumors, were enrolled for the study. They were divided into thymectomy and thymomectomy groups according to the resection extent of the thymus. Demographic and surgical outcomes were compared between the two patients groups. RESULTS: A total of 1, 047 patients were enrolled, with 796 cases in the thymectomy group and 251 cases in the thymomectomy group. Improvement rate of myasthenia gravis (MG) was higher afer thymectomy than afer thymomectomy (91.6% vs 50.0%, P < 0.001). Ten-year overall survival was similar between the two groups (90.9% afer thymectomy and 89.4% afer thymomectomy, P=0.732). Overall, recurrence rate was 3.1% afer thymectomy and 5.4% afer thymomectomy, with no signifcant difference between the two groups (P=0.149). Stratifed analysis revealed no signifcant difference in recurrence rates in Masaoka-Koga stage Ⅰ tumors (3.2% vs 1.4%, P=0.259). However in patients with Masaoka-Koga stage Ⅱ tumors, recurrence was signifcantly less afer thymectomy group than afer thymomectomy (2.9% vs 14.5%, P=0.001). CONCLUSION: Tymectomy, instead of tumor resection alone, should still be recommended as the surgical standard for thymic malignancies, especially for stage Ⅱ tumors and those with concomitant MG.